Transcriptomics and metabolomics analyses provide insights into postharvest ripening and senescence of tomato fruit under low temperature - Chunmei Bai; Caie Wu; Lili Ma; Anzhen Fu; Yanyan Zheng; Jiawei Han; Changbao Li; Shuzhi Yuan; Shufang Zheng; Lipu Gao; Xinhua Zhang; Qing Wang; et al. (Horticultural Plant Journal, 2023)
Tomato is one of the most important vegetable crops in the world and is a model plant used to study the ripening of climacteric fleshy fruit. During the ripening process of tomato fruit, flavor and aroma metabolites, color, texture and plant hormones undergo significant changes. However, low temperatures delayed the ripening process of tomato fruit, inhibiting flavor compounds and ethylene production. Metabolomics and transcriptomics analyses of tomato fruit stored under low temperature (LT, 5 °C) and room temperature (RT, 25 °C) were carried out to investigate the effects of storage temperature on the physiological changes in tomato fruit after harvest. The results of transcriptomics changes revealed that the differentially expressed genes (DEGs) involved in tomato fruit ripening, including several kinds of transcription factors (TFs) (TCP, WRKY, MYB and bZIP), enzymes involved in cell wall metabolism [beta-galactosidase (β-GAL), pectinesterase (PE) and pectate lyase (PL), cellulose and cellulose synthase (CESA)], enzymes associated with fruit flavor and aroma [acetyltransferase (AT), malic enzyme (ME), lipoxygenase(LOX), aldehyde dehydrogenase (ALDH), alcohol dehydrogenase (ADH) and hexokinase (HK)], genes associated with heat stress protein 70 and genes involved in the production of plant hormones such as Ethylene responsive factor 1 (ERF1), Auxin/indoleacetic acids protein (AUX/IAA), gibberellin regulated protein. Based on the above results, we constructed a regulatory network model of the effects of different temperatures during the fruit ripening process. According to the analysis of the metabolomics results, it was found that the contents of many metabolites in tomato fruit were greatly affected by storage temperature, including, organic acids (L-tartaric acid, a-hydroxyisobutyric acid and 4-acetamidobutyric acid), sugars (melezitose, beta-D-lactose, D-sedoheptulose 7-phosphate, 2-deoxyribose 1-phosphate and raffinose) and phenols (coniferin, curcumin and feruloylputrescine). This study revealed the effects of storage temperature on postharvest tomato fruit and provided a basis for further understanding of the molecular biology and biochemistry of fruit ripening.